Geotourism Versus Wellness Tourism or Should We Better Combine Them in Getwell Tourism? A Case Study in Papandayan Compared to Wellness Tourism in Kuningan, West Java, Indonesia - Oman Abdurahman; Andry Edwin Dahlan; Andina Damayanti (International Journal of Geotourism Science and Development, 2022)
In the geotourism program and destination, as the scope of the meaning of geotourism from the experts, it is possible to have other recreational activities that take advantage of the program and the destination area. Both require the importance of conservation and respect for nature and local values in the destination area. Even in geotourism activities carried out in geopark areas, the other recreation can be in the form of activities that support the 10 main program areas in geoparks, as well as the activities in the context of achieving the “Sustainable Development Goals” (SDGs). One other recreation that meets these criteria is health tourism. Thus, instead of being contradicted, between geotourism and health tourism it is very possible to be combined and carried out in one agenda simultaneously with complementary each other. This paper examines an experience of combining the application of one part of health tourism with geotourism travel, hereinafter referred to as getwell tourism program. The location of the application of the getwell tourism is the Papandayan area, an important and well-known geotourism destination in West Java. Aspects of site selection are underlined, as well as the determination of the appropriate health tourism program for the location. In the Papandayan geotourism program, health tours are carried out in the form of earthing, forest therapy, pranayama, and soaking in hot springs. The results were evaluated with the wellness program that had been carried out in Kuningan, West Java and the responses from the participants. It was found that the two types of tourism complement each other and some suggestions for improvement. Thus, getwell tourism is not only possible, it can be applied in almost all geotourism and geopark destinations. Health tourism enriches geotourism and vice versa, and both implementations can be combined in the getwell tourism program.